Scientific production on biogas from cassava processing waste in Brazil: characteristics and approaches - Sacho, Sara Duarte; Zang, Warde Antonieta Fonseca; Zang, Joachim Werner; Hora, Karla Emmanuela Ribeiro (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The presented research proposes an investigation on how scientific production has been carried out regarding biogas produced from cassava processing residues in Brazil. In this direction, a Systematic Literature Review (SLBR) was carried out, inspired by the principles of the methodology proposed by Tranfield et al. (2003). Data was extracted from the articles according to: a) Characterization of publications; and b) Research approach. Thus, it was found that 2018 was the year with the largest scientific publication on the subject; the formation of the main authors is concentrated in the field of Engineering; and publications are especially focused on the state of Paraná. The predominant methodological approach was the Experimental, which prioritized research with the objective of verifying the Efficiency in the production of biogas, according to: a) Co-digestion, inoculum and alkalinizing strategies; b) Performance of operational parameters; and c) Reactor design performance. It was also verified that most articles do not consider the issue of production scale in their research, and when this parameter was considered, it met the large scale of production. Although the Brazilian cassava crop and its processing are marked by a mostly small-scale production, carried out by family farming and destined for internal trade, it appears that this reality was not addressed in any of the articles analyzed.